Positional differences in the most demanding passages of play in football competition - Martin-Garcia, A.; Casamichana, D.; Gómez Diaz, A.; Cos, F.; Gabbett, T. J. (Journal of Sports Science & Medicine, 2018)
The aim of this investigation was to determine the position and duration specific activity of the most demanding passages of play in football players. Global positioning system data were collected from twenty-three football players across a competitive season. A total of 605 individual match files were analysed. Players were categorised based on positional groups; full-back (FB), central defender (CD), midfielder (MF), wide midfielders (WMF) and forwards (FW). The most demanding passage of a match play was analysed using a rolling average method, where maximal values were calculated for four different time durations (1`, 3`, 5` and 10`) using distance (m·min-1), high metabolic load distance (HMLD) and average metabolic power (AMP) as variables of interest. Using distance as the criterion variable, MF and WMF positions covered greater distance, and fewer sprinting meters (>7.0 m·s-1, m·min-1). With HMLD as the criterion variable, the values for WMF and MF positions were higher than the CD and FW positions. The MF and WMF positions performed more high-intensity accelerations and decelerations when the criterion variable was AMP. These results provide an understanding of the most demanding passages of play to inform training practices for specific football playing positions.